2020
DOI: 10.31289/biolink.v7i1.3416
|View full text |Cite
|
Sign up to set email alerts
|

FORMULATION AND ANTIBACTERIAL TEST OF STAR ANISE EXTRACT (Illicium verum Hook.F) AS A HAND SANITIZER

Abstract: The hand becomes one of the body parts that are easily exposed to microorganisms because of their high mobility. Hand sanitizer is a liquid that can be used to kill microbes. Hands become one of the body parts that are easily exposed to microorganisms because of their high mobility. Hand sanitizer is a liquid that can be used to kill microorganisms. Most hand sanitizers contain alcohol and triclosan, which can be bad for the skin if used in excessive amounts. It is necessary to substitute alcohol and triclosan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…In 1998, Sy and Brown isolated novel lignans from anise leaves (98-102 and 105-107) [66], and later these compounds were also found in anise fruits [67,69]. The compounds verimol A (98) and harmandianone (92) showed concentration-dependent significant inhibition of lipopolysaccharide-induced tumour necrosis factor production in RAW264.7 cells [69]. Compounds 96, 97, 103, 104, 108, 111 and 112 are known lignan-like compounds that are found in anise [67,73].…”
Section: Phenylpropanoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1998, Sy and Brown isolated novel lignans from anise leaves (98-102 and 105-107) [66], and later these compounds were also found in anise fruits [67,69]. The compounds verimol A (98) and harmandianone (92) showed concentration-dependent significant inhibition of lipopolysaccharide-induced tumour necrosis factor production in RAW264.7 cells [69]. Compounds 96, 97, 103, 104, 108, 111 and 112 are known lignan-like compounds that are found in anise [67,73].…”
Section: Phenylpropanoidsmentioning
confidence: 99%
“…For instance, Aceh curry, Rendang Minang, Javanese cuisines and Balinese cuisines employ star anise. In northern China, star anise is one of the most popular seasonings, and it can be used directly in a variety of food preparations such as stewing, boiling, pickling, brining and soaking, or it can be processed into a five-spice seasoning powder [92]. Star anise extracts have the advantages of being natural, non-toxic and harmless, and they are usually used in the food industry to produce various food flavors.…”
Section: Modern and Traditional Uses Of Star Anisementioning
confidence: 99%
“…Dimana hasil dari penelitian ini didapatkan rentang nilai rata-rata pH sediaan ada pada 8,67-9,80 yang dimana masuk kedalam kategori basa lemah. Seharusnya sediaan spray gel yang diformulasikan memiliki kisaran pH sesuai dengan pH kulit yakni pH 4,5-6,5 sehingga tidak menimbulkan efek negatif pada kulit, dikarenakan sediaan ini memiliki pH tinggi, maka berpotensi akan berpengaruh pada elastisitas kulit serta menyebabkan kulit licin dan cepat kering [13].…”
Section: Hasil Dan Pembahasanunclassified
“…Modern pharmacological investigations demonstrated that I. verum possessed antiviral, , antioxidant, , antitumor, , antibacterial, , insecticidal, , anti-inflammatory, , analgesic, and neuroprotective activities. Previous phytochemical studies on I.…”
Section: Introductionmentioning
confidence: 99%